Big Data Analytics in Healthcare - Lazebnyk Iuliia O. (Problemi Ekonomiki, 2018)
Particular attention is paid to identifying possibilities for analyzing big data by healthcare organizations as well as to studying potential benefits that can be received due to the modern understanding of big data analytics and the ways for innovative transformation of organizations in terms of management information. It is substantiated that the use of big data analytics in the field of healthcare is one of the promising areas for the implementation of innovative approaches in the social sphere. For this purpose, various components of big data analytics are considered, in particular, descriptive and predictive analytics. Several approaches to identifying possibilities of introducing big data analytics are analyzed. The main sources of big data and possible directions of their use in the healthcare system are identified. The main obstacles that hinder widespread introduction of big data are highlighted. The ways to improve the efficiency of analytical and predictive capabilities of big data are outlined.